China Imagined : From European Fantasy to Spectacular Power - Lee, Gregory B. (London : Hurst & Company, 2018)
If 'China', as Lee argues, is a product of Westernisation, then the West is itself in a process of becoming China. How did China become China? And where is it leading us? We talk as if it had always existed: eternal China with its 5,000 years of uninterrupted history. But the name 'China' was first used by 16th-century Europeans, and its Chinese equivalent, Zhongguo, only gained currency in the mid-1800s. 'China Imagined' is a thoughtful exploration of the idea of China, from the naming and mapping of its territory and peoples to the creation and rise of the modern nation-state.
Includes bibliographical references (pages 213-221) and index.
Keywords: Acculturation -- China; China -- History; China -- Civilization; China; History